Development and Validation of Fast and Simple Fourier Transform Infrared Spectrophotometric Method for Analysis of Thiamphenicol in Capsule Dosage Form - Nerdy Nerdy; Linda Margata; Nilsya Febrika Zebua; Puji Lestari; Tedy Kurniawan Bakri; Faisal Yusuf; Vonna Aulianshah (Science and Technology Indonesia, 2023)
The development of a method for identification and determination of thiamphenicol by Fourier Transform Infrared will provide convenience to developers because it is fast and easy for analysis. The research was carried out by utilizing the solubility of thiamphenicol in methanol with three stages, namely method development, sample analysis, and method validation. The method development stage showed that the specific peak of thiamphenicol was at a peak with a wavenumber of 1694.1 cm−1; this specific peak of thiamphenicol was used for qualitative analysis and quantitative analysis of thiamphenicol in the capsule dosage form. The sample analysis showed that all analyzed thiamphenicol in capsule dosage form showed good results both qualitatively and quantitatively. Qualitatively all the samples analyzed showed a specific peak at specific positions and specific wavenumbers. These results meet the requirements for containing thiamphenicol in the dosage form. Quantitatively all the samples analyzed ranged from 97.97% to 102.24% by peak height and peak area. These results meet the requirements for active substance levels in general preparations within 90.0% to 110.0%. The method validation for peak height and peak area showed that the accuracy parameter had a recovery percentage of 100.28% and 100.41% (between 98.0% to 102.0%), the precision parameter with a relative standard deviation of 0.31% and 0.37% (not more than 2.0%), and the linearity parameter with a correlation coefficient of 0.9999 and 0.9997 (not less than 0.99). The limit of detection value was 0.2971 mg/mL and 0.5338 mg/mL, the limit of quantitation value was 0.9004 mg/mL and 1.6176 mg/mL, the range for both was 80% to 120%, and the specificity for both met the requirement. The Fourier Transform Infrared method has been successfully developed, applied, and validated for qualitative analysis and quantitative analysis of thiamphenicol in capsule dosage form.